Visual network analysis of research hotspots and trends in post-stroke fatigue among the elderly based on bibliometrics - LAI Lichong; WEI Jinjin; HUANG Dongmei; PAN Qini; CHEN Xiaoxia; HUANG Huiqiao (Guangxi Yike Daxue xuebao)
Objective To conduct a visual analysis of the research status, hotspots, and trends in the literature related to post-stroke fatigue (PSF) in the elderly over the past decade, so as to provide a reference for subsequent studies. Methods The Web of Science Core Collection was searched to collect literature on PSF in the elderly published between January 1, 2014 and December 31, 2023. The Bibliometric package in R software and CiteSpace 6.3.R1 software were utilized to generate and interpret visual maps of publication output, institutions, keywords, and co-cited documents. Results A total of 805 articles were included, involving 67 countries/regions, 294 institutions and 305 authors. The United States had the highest number of publications and centrality, indicating a need for strengthened regional and institutional collaboration globally. The research themes formed five highly clustered keyword groups: depression, rehabilitation therapy, chronic diseases, quality of life, and measurement tools. The keyword four-quadrant diagram revealed that quality of life, depression, performance response, skeletal muscle, and stroke volume per beat were important topics with promising development prospects in this field. Meanwhile, heart failure, mechanisms, measurement methods and scales, as well as self-management were crucial topics that had not yet achieved substantial progress. The major burst words in the past five years included depression, quality of life, risk factors, exercise rehabilitation, effectiveness, and social impact. The clustered terms of cited documents encompassed chronic diseases, health-related quality of life, and longitudinal studies. Conclusion Research hotspots in the field of PSF in the elderly primarily focus on prognosis rehabilitation and psychological nursing. Future endeavors can further explore predictive nursing and the development of assessment tools that integrate subjective and objective measures, catering to patients'individualized needs and establishing a comprehensive rehabilitation nursing practice system for PSF in the elderly.